Malta : 2013 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2013)
This staff report on Malta's Article IV Consultation highlights economic development and policies. Risks from the large international bank sector appear contained given limited balance-sheet exposure to the Maltese economy, though continued vigilance is warranted. Regulatory changes to increase loan loss provisions, and the funding of the deposit compensation scheme would help contain risks in the domestic banking sector. The main challenges for fiscal policy are to reverse the deterioration of public finances, and to strengthen the governance framework. Additional measures are needed to ensure that the fiscal deficit falls below 3 percent of GDP in 2013 and that public debt remains on a sustainable path.